7 - Adolescent Sexuality and Culture: South African Mothers` Perspective - Pilot Mudhovozi; Mpho Ramarumo; Tholene Sodi (African Sociological Review, 2013)
This study explores South African mothers’ perspective on adolescent sexuality within their cultural prism. Forty-four (44) mothers were purposefully selected for the study. Data was collected through six focus group discussions. The results indicated that culturally embedded reasons inhibited mothers from effectively imparting knowledge about sexuality to their daughters. Insufficient information, lack of role models and fear of sensitising their daughters to sexuality issues were other inhibitory factors.